Linguística e ensino: o discurso de entremeio na formação de professores de língua portuguesa - Luz, Mary Neiva Surdi da (2010)
This study aims at investigating how and which theoretical aspects of linguistics are effective for implementing a Letters course directed across the educations of Portuguese language teachers. This doctoral dissertation is anchored to a theoretical-methodological perspective of the French discourse analysis which dialogues with the History of Linguistic Ideas. Our analysis is carried out through a documental investigation of a corpus of analysis containing accounts on the Letters course, specifically at UNOCHAPECÓ a community college in Santa Catarina, Brazil. In this study we looked upon the constitution of such course considering the faculty of this institution and the disciplinary organization of the syllabuses referring to the following subjects: Portuguese language; Comprehension and written production, Linguistics and Linguistic Studies as being representatives of distinct moments of the course. Also, we established theoretical categories with the purpose of identifying the inter and intradiscourses related to these subjects as an analytical-oriented practice. By means of this documental analysis, we pointed out the following most important aspects: the foundation of higher education in the western part Santa Catarina is characterized by being supported by education foundations and in their constitution it is observed a distinguishable difference from the model of higher education if compared to the rest of the country. This course here being mentioned is legally bound to obey the common legislation of the State and in the late 1980s, taking into account the need of the local communities for qualified professionals, the faculty members in these institutions started being characterized by being locally trained. As a result of this characteristic, the syllabuses were changed in order to comply with the local market need and the current legislation. Regarding the syllabuses of the curricular subjects, we came across the following categories of analysis; (pro)fusion of knowledges, (con)fusion of knowledges, identification and confrontation of knowledges and pedagogization of knowledges. We understand that the relations among the concepts , (pro)fusion of knowledges, (con)fusion of knowledges, identification and confrontation of knowledges and pedagogization of knowledges are established at their constitutional level, referring to how the interdiscourse works while compared to what was produced and what was reproduced. Within these relations we also observed how the intradiscourse is built in the sense of articulating what was fully understood in the interdiscourse. The way these knowledge relations work together with the purpose of finding a middle-ground between the inter-winding nature of Linguistics and teaching, and how this inter-winding natures is characterized by an intradiscoursive articulation, is the only possible way to work at an interdiscoursive level, as a means of broadening the object of linguistics.